Cannabis alters DNA methylation at maternally imprinted and autism candidate genes in spermatogenic cells. (2nd November 2022) - Schrott, Rose; Greeson, Katherine W.; King, Dillon; Symosko Crow, Krista M.; Easley, Charles A.; Murphy, Susan K.
Abstract: Cannabis use in the United States is increasing, with highest consumption among men at their peak reproductive years. We previously demonstrated widespread changes in sperm DNA methylation with cannabis exposure in humans and rats, including genes important in neurodevelopment. Here, we use an in vitro human spermatogenesis model to recapitulate chronic cannabis use and assess DNA methylation at imprinted and autism spectrum disorder (ASD) candidate genes in spermatogonial stem cell (SSC)- and spermatid-like cells. Methylation at maternally imprinted genes SGCE and GRB10 was significantly altered in SSC- and spermatid-like cells, respectively, while PEG3 was significantly differentially methylated in spermatid-like cells. Two of ten randomly selected ASD candidate genes, HCN1 and NR4A2, had significantly altered methylation with cannabis exposure in SSC-like cells. These results support our findings in human cohorts and provide a new tool with which to gain mechanistic insights into the association between paternal cannabis use and risk of ASD in offspring.